Nitrogen fixation [ global perspectives : proceedings of the 13th International Congress on Nitrogen Fixation, Hamilton, Ontario, Canada, 2-7 July 2001 - Finan, Turlough M. (CABI, 2002)
This volume presents the proceedings of the 13th International Congress on Nitrogen Fixation, held in Hamilton, Ontario, Canada, in July 2001. It covers molecular and biochemical aspects, plant genomics, stresses and factors limiting nitrogen fixation, nd applied aspects.